2,5*(2-3x)+6,3x=3*(1,2-0,6x)+1,1

Simple and best practice solution for 2,5*(2-3x)+6,3x=3*(1,2-0,6x)+1,1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2,5*(2-3x)+6,3x=3*(1,2-0,6x)+1,1 equation:



2.5(2-3x)+6.3x=3(1.2-0.6x)+1.1
We move all terms to the left:
2.5(2-3x)+6.3x-(3(1.2-0.6x)+1.1)=0
We add all the numbers together, and all the variables
2.5(-3x+2)+6.3x-(3(-0.6x+1.2)+1.1)=0
We add all the numbers together, and all the variables
6.3x+2.5(-3x+2)-(3(-0.6x+1.2)+1.1)=0
We multiply parentheses
6.3x-7.5x-(3(-0.6x+1.2)+1.1)+5=0
We calculate terms in parentheses: -(3(-0.6x+1.2)+1.1), so:
3(-0.6x+1.2)+1.1
We multiply parentheses
0x+3.6+1.1
We add all the numbers together, and all the variables
x+4.7
Back to the equation:
-(x+4.7)
We add all the numbers together, and all the variables
-1.2x-(x+4.7)+5=0
We get rid of parentheses
-1.2x-x-4.7+5=0
We add all the numbers together, and all the variables
-2.2x+0.3=0
We move all terms containing x to the left, all other terms to the right
-2.2x=-0.3
x=-0.3/-2.2
x=0.3/2.2

See similar equations:

| t-44=32 | | 27=13+y | | 7r+-20r+4=17 | | 17x-25=17(4)-25 | | 15h+20=20h+10 | | 0.5(8x-10)=4x-5 | | 4x-12=132 | | 29+3x=7 | | (8x-14)+(2x+4)=180 | | -8.8=w-(-1.1) | | 16/32=x/24 | | 14s+2=4 | | 30=5/7u | | 9h-5h+4=20 | | 3(x-4)=6(2x+3) | | 17x+8+7x+4=180 | | 180=2x+96+x+12 | | (2m-2)(4m-8)=0 | | 560=11x+x | | x-3=7x-15 | | 5(2y+4)=20 | | 90-18x=x+52 | | 6(1+7x)-7(1+6x)=-1 | | 3.5=m-2 | | 25.69=2x-6.32 | | 13=14y | | 6−9x=7x−10x−126-9 | | 3x+7-2+2x=15 | | 4(q-14)+2=18 | | C+9=20;9=c | | 45=-10x+95 | | l=180-45 |

Equations solver categories